2017
DOI: 10.1088/0256-307x/34/7/077802
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Radiation Sensing Properties of ZnS Thin Film: A Study on the Effect of Annealing

Abstract: Chemically synthesized ZnS thin film is found to be a good x-ray radiation sensor. We report the effect of annealing on the x-ray radiation detection sensitivity of a ZnS thin film synthesized by a chemical bath deposition technique. The chemically synthesized ZnS films are annealed at 333, 363 and 393 K for 1 h. Structural analyses show that the lattice defects in the films decrease with annealing. Further, the band gap is also found to decrease from 3.38 to 3.21 eV after annealing at 393 K. Current-voltage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…An increase in conductivity could be ascribed to a decrease in the grain boundary as well as the band gap of the material. A similar increase in conductivity with annealing was also observed in the ZnS film [29].…”
Section: Current-voltage (I-v) Characteristicssupporting
confidence: 77%
“…An increase in conductivity could be ascribed to a decrease in the grain boundary as well as the band gap of the material. A similar increase in conductivity with annealing was also observed in the ZnS film [29].…”
Section: Current-voltage (I-v) Characteristicssupporting
confidence: 77%
“…In recent times, the use of wide band gap semiconductors for X-ray detection has emerged due to their natural hardness, low dark currents, and ability to sustain high electric fields . Some notable examples of wide band gap materials thst are investigated for X-ray detection are GaN, SiC, β-Ga 2 O 3 , amorphous Ga 2 O 3 (a-Ga 2 O 3 ), ZnO, TiO 2 , and ZnS. , Among these, the ZnO based sensors have attracted much attention due to its simple method of synthesis, good transparency over the visible light and high radiation hardness. , Several studies on ZnO based X-ray sensors have been reported that encourage its application for flat panel X-ray imaging detectors. However, optimization of its properties for X-ray sensitivity and feasibility of its fabrication to attain the commercial standard are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…12 Some notable examples of wide band gap materials thst are investigated for X-ray detection are GaN, 13 SiC, 14 β-Ga 2 O 3 , 15 amorphous Ga 2 O 3 (a-Ga 2 O 3 ), 16 ZnO, 17−21 TiO 2 , 22 and ZnS. 23,24 Among these, the ZnO based sensors have attracted much attention due to its simple method of synthesis, good transparency over the visible light and high radiation hardness. 18,20 Several studies on ZnO based X-ray sensors have been reported that encourage its application for flat panel X-ray imaging detectors.…”
Section: Introductionmentioning
confidence: 99%